PUBLIC DEBT AND FINANCIAL SECURITY OF UZBEKISTAN (E Conference Zone, 2022)
This article is devoted to the description of the socio-economic essence of financial security, public external debt, the level of protection of financial interests at the macro level, which analyzes the indicator of financial security in the country - the current state of public debt, its impact on the country's financial security system. Attention is also paid to solving existing problems in the system of state financial security of the Republic of Uzbekistan.